Risk Preferences and the Economics of Contracts - Allen, Douglas W.; Lueck, Dean (The American economic review, 1995)
Assumptions of risk aversion in modern economics are pervasive, and economists who substitute risk neutrality often do so with an apology. This is particularly true for contract theories, like the principal-agent model. Despite the theoretical prominence of risk aversion, empirical contract studies tend to ignore risk preferences and focus exclusively on transaction costs, thus stressing specific incentives, enforcement costs, and transaction-specific assets. Accumulated evidence confronting risk-sharing and transaction costs - covering such topics as franchising, gold mining, sharecropping, and timber - actually favors the transaction-cost framework. Risk preferences in contract theory and the evidence failing to support theories relying on risk-averse agents are examined.